Triterpenoid Saponins from Two Panax japonicus Varietals Used in Tujia Ethnomedicine - Liu, Yang; Chan, Michael; Huang, Jianhua; Li, Bin; Ouyang, Wen; Peng, Caiyun; Liao, Duanfang; Wang, Wei (Current Traditional Medicine, 2015)
Tujia ethnomedicine is an important part of the national medicine system in China. Two Panax japonicus (Araliaceae) varietals known as Bai San Qi and Kou Zi Qi in Tujia ethnomedicine are of interest for further study due to their traditional use, biological effects and potential use in clinical applications. The plants have traditionally been used to treat weakness, fatigue and rheumatism for over a thousand years. As Bai San Qi and Kou Zi Qi are members of the genus Panax, both contain significant levels of saponins. Saponins have been shown to have a variety of bioactivities including, antiinflammatory, anti-tumor and α-glucosidase inhibitory activities. Thus far, 109 different saponins have been isolated from and identified in the two plants. This review describes, classifies and provides information on reported biological activities and characteristic 1H-NMR and 13C-NMR signals for the saponins found in the two species. It aims to decrease the difficulties in structure elucidation of typical saponins and provides instruction and theoretical basis for further research of the two plants.
Keywords: zhu jie shen